Non-Canonical NF-κB Signaling Initiated by BAFF Influences B Cell Biology at Multiple Junctures - Gardam, Sandra; Brink, Robert (Frontiers in Immunology, 2014)
It has been more than a decade since it was recognised that the nuclear factor of kappa light polypeptide gene enhancer in B cells (NF-κB) transcription factor family was activated by two distinct pathways: the canonical pathway involving NF-κB1 and the non-canonical pathway involving NF-κB2. During this time a great deal of evidence has been amassed on the ligands and receptors that activate these pathways, the cytoplasmic adapter molecules involved in transducing the signals from receptors to nucleus, and the resulting physiological outcomes within body tissues. In contrast to NF-κB1 signalling, which can be activated by a wide variety of receptors, the NF-κB2 pathway is typically only activated by a subset of receptor and ligand pairs belonging to the tumour necrosis factor (TNF) family. Amongst these is B cell activating factor of the TNF family (BAFF) and its receptor BAFFR. Whilst BAFF is produced by many cell types throughout the body, BAFFR expression appears to be restricted to the haematopoietic lineage and B cells in particular. For this reason, the main physiological outcomes of BAFF-mediated NF-κB2 activation are confined to B cells. Indeed BAFF mediated NF-κB2 signalling contributes to peripheral B cell survival and maturation as well as playing a role in antibody responses and long-term maintenance plasma cells. Thus the importance BAFF and NF-κB2 permeates the entire B cell lifespan and impacts on this important component of the immune system in a variety of ways.